The evolution of Palaeolake Flixton and the environmental context of Star Carr: an oxygen and carbon isotopic record of environmental change for the early Holocene. Issue 1 (February 2015) - Candy, I.; Farry, A.; Darvill, C.M.; Palmer, A.; Blockley, S.P.E.; Matthews, I.P.; MacLeod, A.; Deeprose, L.; Farley, N.; Kearney, R.; Conneller, C.; Taylor, B.; et al.
Abstract This paper presents δ18O and δ13C values from three early Holocene lacustrine carbonate sequences from Palaeolake Flixton in northeastern England. The δ13C values are typical of carbonates precipitating in an open lake system with the exception of samples from the very uppermost parts of these sequences which have values more typical of palustrine or tufaceous carbonates and, therefore, indicate the progressive contraction and shrinkage of the lake system overtime. The δ18O values record an initial increase to an early peak at the onset of the Holocene but a subsequent decline in values of such a magnitude that by ca 8000 yrs B.P. the δ18O value of the precipitated carbonate is consistent with carbonates that precipitated at the end of the Loch Lomond Stadial. The early increase and peak in δ18O values is suggested to reflect the climatic amelioration at the onset of the Holocene, as temperatures progressively rose. The decline cannot be explained by any known temperature shifts, however, this "depletion trend" is seen in several other early Holocene lacustrine records from across the British Isles. This decline is suggested to reflect a shift in the seasonality of precipitation from a more seasonal precipitation regime typical of a "continental" climate, with strong seasonal contrasts in rainfall, to a more "maritime" climate which was characterised by consistent levels of rainfall occurring across the year. The relative timing of human activity at Star Carr suggests human occupation occurred after this isotopic decline under "maritime" rather than "continental" climates.